Using Mixed Reality and Adaptive Learning to Enhance Understanding of Algebraic Concepts with the Help of GeoGebra - Rahmatika, Ahmad (Holistic Science, 2023)
Utilizing mixed reality and adaptive learning to enhance the understanding of algebraic concepts, using GeoGebra as a tool. The research design involved an experimental group engaged in technology-integrated learning and a control group following conventional learning. Data were collected through pre-post tests and observations of student interactions with GeoGebra. The analysis results indicate that the experimental group experienced a significant improvement in the understanding of algebraic concepts compared to the control group. Students in the experimental group also showed higher engagement and positive responses to the use of mixed reality and adaptive learning. This research supports the idea that GeoGebra, when integrated with mixed reality and adaptive learning approaches, can create a more dynamic and effective learning experience in enhancing students' understanding of algebraic concepts. The implications of this research involve the potential development of innovative mathematics learning strategies to improve student learning outcomes.